The Influence of Workload on Lecturer Performance through Job Satisfaction at the IT&B Medan Campus - Adi Harianto (Yayasan Bina Bisnis Nusantara Medan, 2024)
This study seeks to examine the impact of workload on professor performance via job satisfaction at the IT&B Medan Campus. In higher education, an increase in professor workload can impact the quality of instruction and research. This research utilizes a quantitative survey methodology, disseminating questionnaires to instructors at the IT&B Campus for data collection. The research results reveal that workload does not significantly impact professor job satisfaction, suggesting that lecturers effectively manage their obligations despite a high workload. Moreover, workload did not significantly impact professor performance, suggesting that instructors at the IT&B Medan Campus can sustain their academic success despite the pressures of strain. Job happiness significantly influences lecturer performance, with pleased lecturers exhibiting more motivation to deliver outstanding instruction. The study's results indicate that job happiness does not mediate the relationship between workload and lecturer performance. This conclusion underscores the necessity of fostering a supportive and encouraging work environment for lecturers, despite the fact that a high workload does not directly influence their satisfaction and performance. This research offers insights for the administration of the IT&B Medan Campus to enhance educational quality via improved human resource management